Wpływ inicjatyw społecznych przedsiębiorstw na reakcje konsumentów - Zasuwa, Grzegorz (The Influence of Corporate Social Initiatives on Consumers' Reactions, 2009)
The task of this article is to discuss the influence of corporate social initiatives on consumers' reactions. The paper is divided into two parts. The first one contains a review of relevant publications dealing with the problem of consumer reactions towards corporate social initiatives. The second one focuses on determinants of consumers' reactions. The analysis has shown that corporate social initiatives can influence on various consumers' reactions, such as corporate attitudes, purchase intentions, loyalty and other reactions. However, only some corporate social initiatives lead to positive consumers' behaviour. In fact, the process of consumers' reactions toward pro-social initiatives is very complicated and depends on a lot of variables. The analysis has suggested that it can depend on the structure of social programmes, consumers' characteristics and communications.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 248-258